The holistic career coaching handbook : a guide to providing the right environment for all employees to thrive - Nathan, Robert (Routledge, 2025)
"Exclusion from the workplace not only has devastating effects on individual wellbeing and public health, but also limits organisational development and social cohesion. This book promotes an understanding of the strengths of people with diverse attributes, transforming a sense of being overlooked by employers to being a valued asset. This handbook provides tools for people to respond respectfully to the way employees experience their working lives. It guides the reader to realise the potential strengths of employees, regardless of their background, life situation, mental health or neurological condition, and appreciate the impact of emotions on their contribution to and experience of work. Other books look at organisational reasons for motivation; this book addresses the emotional effect of significant change outside the workplace that has an impact on motivation at work. Chapters cover Neurodiversity, Parental coaching, Career Returners, Menopause and the impact of different life stages. This practical book uses cases and summaries throughout and has chapters on creating a successful programme of career support, together with 15 original Career Tools. It is particularly relevant to Human Resources, Learning and Development, and Line Managers, and anyone wanting to develop effective in-house career coaching for employees"-- Provided by publisher.
Keywords: Vocational guidance.; Career development.; elektronické knihy; electronic books